Tiếng Anh Kinh tế - Bộ môn Tiếng Anh (Trường Đại học Thuỷ Lợi, 2020)
Contents: Chapter 1: Letter layout, content and style; Chapter 2: Enquiries & Replies; Chapter 3: Offer and cover letter of offer; Chapter 4: Orders and Cover Letters of Orders; Chapter 5: Complaints and Adjustments; Chapter 6: Payments in International Trade; Chapter 7: Transportation